Resolvin D2 Restrains Th1 Immunity and Prevents Alveolar Bone Loss in Murine Periodontitis - Mizraji, Gabriel; Heyman, Oded; Van Dyke, Thomas E.; Wilensky, Asaf (Frontiers in Immunology, 2018)
Periodontitis is an infectious inflammatory disease of the supporting structures of the teeth. Resolvins are part of a large family of specialized pro-resolving lipid mediators that enhance active resolution of inflammation and return of inflammatory lesions to homeostasis. In this paper, we demonstrate that resolvin D2 (RvD2), a product of docosahexaenoic acid (DHA) metabolism, prevents alveolar bone loss in Porphyromonas gingivalis-induced experimental periodontitis. Investigations of the immune mechanism of RvD2 actions reveal that six weeks after infection, the gingiva of RvD2-treated mice exhibit decreased CD4+ T cells as well as lower RANKL expression levels and higher OPG expression levels. Systemically, RvD2 prevents chronic secretion of IFN-γ and rapidly restores IFN-α levels, without dampening the Porphyromonas gingivalis-specific immune response. In the gingiva, immediately after Porphyromonas gingivalis inoculation, RvD2 regulates the mRNA expression of IFN-ɣ, IL-1β, TNF-α and IL-10, hence contributing to maintaining local homeostasis. Moreover, RvD2 treatment reduces local neutrophil numbers, whereas pro-resolving macrophage counts were increased. These findings suggest that RvD2 resolves innate inflammatory responses, inhibiting systemic and gingival Th1-type adaptive responses that are known to mediate alveolar bone loss in this model.